The effects of unilateral posterior crossbite toward the superficial masseter and anterior temporalis on muscle activity during mastication: A surface electromyographic study - Agnes Imelda Izach; C. Christnawati; Darmawan Susantyo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Adapted patterns of mastication caused by unilateral posterior crossbite require early orthodontic treatment to prevent permanent muscle change. Stable orthodontic results depend on the harmonious contraction of the occlusion and masticatory muscles. Purpose: Using surface electromyography, this study aimed to analyse the effects of unilateral posterior crossbite on the superficial masseter as well as anterior temporalis muscle activity on the crossbite and non-crossbite sides during chewing soft and hard foods. Methods: A cross-sectional study was conducted on 20 subjects with at least two posterior teeth who had a unilateral posterior crossbite without mandible shifting. Surface electromyography was used to measure activity amplitudes for the superficial masseter and the anterior temporalis muscles while chewing soft and hard foods. An independent t-test was used to determine the mean difference between chewing soft and hard foods through the superficial masseter and anterior temporalis muscles. Results: Results showed a significant difference in amplitude mean between crossbite and non-crossbite sides of the superficial masseter and anterior temporalis muscles with both soft and hard food chewing (p < 0.05). The study also revealed a decrease in the activities of superficial masseter and anterior temporalis muscles when masticating soft and hard foods on the crossbite sides as compared to the non-crossbite sides. Conclusion: A unilateral posterior crossbite results in a decrease in the superficial masseter and the anterior temporalis muscle activity when masticating both soft and hard foods on the crossbite side.